2005
DOI: 10.1128/aem.71.11.7610-7612.2005
|View full text |Cite
|
Sign up to set email alerts
|

When Coupled to Natural Transformation inAcinetobactersp. Strain ADP1, PCR Mutagenesis Is Made Less Random by Mismatch Repair

Abstract: Random PCR mutagenesis is a powerful tool for structure-function analysis of targeted proteins, especially when coupled with DNA integration through natural transformation followed by selection for loss of function. The technique has been applied successfully to structure-function analysis of transcriptional regulators, enzymes, and transporters in Acinetobacter sp. strain ADP1. However, the mismatch repair system prevents the full spectrum of nucleotide substitutions that may be selected at the level of prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…This was first of several genes identified that encode enzymes that directly consume DMSP, the details of which are discussed below. Many of these studies were performed in cultured representatives of the well-studied roseobacters, a phylogenetically coherent clade of clade of Alphaproteobacteria that are mostly marine in origin (Buchan et al, 2005; Wagner-Dobler and Biebl, 2006). …”
Section: Introductionmentioning
confidence: 99%
“…This was first of several genes identified that encode enzymes that directly consume DMSP, the details of which are discussed below. Many of these studies were performed in cultured representatives of the well-studied roseobacters, a phylogenetically coherent clade of clade of Alphaproteobacteria that are mostly marine in origin (Buchan et al, 2005; Wagner-Dobler and Biebl, 2006). …”
Section: Introductionmentioning
confidence: 99%
“…Facile engineering of the ADP1 genome to edit and add to metabolic and sensing pathways is made possible by its constitutive expression of a competence apparatus that enables it to efficiently take up DNA from its environment in a non-sequence-specific manner (11). ADP1 can also transform fragmented and damaged DNA or mutagenized PCR products to introduce sequence variation at specific sites in its genome for optimizing engineered functions (12,13).…”
mentioning
confidence: 99%
“…As a model soil microorganism with strong natural transformation competence, A. baylyi ADP1 has been fully sequenced (Barbe et al, 2004) and studied for decades (Hare and Gregg-Jolly, 2003;Metzgar et al, 2004;Zheng and Gregg-Jolly, 2004;Buchan and Ornston, 2005). Although A. baylyi ADP1 cells have been previously constructed as hosts for DNA damage responsive whole-cell bioreporters in environmental toxicity assessment (Ammerman and Azam, 1987;Barbe et al, 2004;Song et al, 2009;Jiang et al, 2014Jiang et al, , 2017Jia et al, 2016), the DNA damage response network in A. baylyi ADP1 is still not well-established.…”
Section: Different Behavior Of Protein Profiles In Different Carbon Smentioning
confidence: 99%